KEKUATAN AGENSI KREDIT MIKRO DALAM MEMBANTU PEDAGANG KECIL STUDI KASUS : BAITUL MAL WAT-TAMWIL DI RIAU PEROVINSI - Saib, Khaidir (Eko dan Bisnis: Riau Economic and Business Review, 2018)
Baitul Mal wat-Tamwil is one of the microcredit agencies introduced in Riau Region in 1987. The establishment of BMT in Riau is very easy and the number is quite a lot, it is 84 units. The manifestation of Baitul Mal wat-Tamwil continues to prevail and operate well. He is in charge of building a small peniaga. However, the facts show that some BMTs are inactive and problematic. The impression is that customer problems that require capital can not be solved because BMT does not have the ability to run its role as a micro credit agency. This study aims to identify the viability, strengths and weaknesses of microcredit agencies in fostering small traders in Riau Province. This study answers the following three issues: 1) What affects the power of Baitul Mal wat-Tamwil in carrying out its operations. A qualitative approach to severity studies was selected to refine and address the study question. Approach and method is chosen because he is able to answer the problem of study that wants to know the factor of business continuity Baitul Mal wat-Tamwil. The structured technique is used to collect data from nine BMT executives who share their experiences in carrying out the DGH operation. The data has been analyzed by fostering themes and categories to answer the study questions. The findings of the study found that the factors that power Baitul mal wat Tamwil are: 1) Smaller trading pedestal, 2) labor cooperation